Inhibition of IL17A Using an Affibody Molecule Attenuates Inflammation in ApoE-Deficient Mice - Kumawat, Ashok Kumar; Zegeye, Mulugeta M.; Paramel, Geena Varghese; Baumgartner, Roland; Gisterå, Anton; Amegavie, Obed; Hellberg, Sanna; Jin, Hong; Caravaca, April S.; Söderström, Leif Å.; Gudmundsdotter, Lindvi; Frejd, Fredrik Y.; et al. (Frontiers in Cardiovascular Medicine, 2022)
The balance between pro- and anti-inflammatory cytokines released by immune and non-immune cells plays a decisive role in the progression of atherosclerosis. Interleukin (IL)-17A has been shown to accelerate atherosclerosis. In this study we investigated the effect on pro-inflammatory mediators and atherosclerosis development of an Affibody molecule that targets IL17A. Affibody molecule neutralising IL17A, or sham were administered in vitro to human aortic smooth muscle cells (HAoSMCs) and murine NIH/3T3 fibroblasts and in vivo to atherosclerosis-prone, hyperlipidaemic ApoE-/- mice. Levels of mediators of inflammation and development of atherosclerosis were compared between treatments. Exposure of human smooth muscle cells and murine NIH/3T3 fibroblasts in vitro to IL-17A Affibody molecule markedly reduced IL6 and CXCL1 release in supernatants compared with sham exposure. Treatment of ApoE-/- mice with IL-17A Affibody molecule significantly reduced plasma protein levels of CXCL1, CCL2, CCL3, HGF, PDGFB, MAP2K6, QDPR and splenocyte mRNA levels of Ccxl1, Il6 and Ccl20 compared with sham exposure. There was no significant difference in atherosclerosis burden between the groups. In conclusion, administration of IL17A Affibody molecule reduced levels of pro-inflammatory mediators and attenuated vascular inflammation in ApoE-/- mice.